Extraction of tiger nut oil using ultrasound-assisted immiscible binary solvents and its effect on the quality of extracted oil and starch - Zhi-cheng Li; Zhen-shan Zhang; Ying Xia; Jin-tao Han; Hua-zhang Chang; Hui-min Wang (Ultrasonics Sonochemistry)
Tiger nuts are rich in both oil and starch. In this paper, an immiscible binary solvent consisted of water and hexane was used to separate oil and starch from tiger nut with the assistance of ultrasound. The effects of various factors including ultrasonic power, ultrasonic time, extraction temperature, water-hexane ratio and solid–liquid ratio on the oil yield were examined. The oil and starch obtained were characterized and compared with those obtained through conventional methods, such as mechanical pressing (MP) and solvent extraction (SE). The results indicated that all examined factors, especially water-hexane ratio significantly affected the oil yield. Under the optimum conditions, ultrasound-assisted immiscible binary solvent extraction (UASE) yielded more oil than SE and MP. The quality analysis revealed that the acid value and iodine value of UASE oil were comparable to those extracted using the MP and SE methods, but the peroxide value was lower, and the vitamin E content was higher. In addition, the starch from tiger nut after UASE exhibited lower viscosity, greater solubility and swelling power, and better thermal and freeze–thaw stability. This study demonstrated that the UASE method is an efficient and environmentally friendly technique for simultaneously extracting oil and starch from tiger nuts.